Transformation through the implementation of the merdeka curriculum for learning recovery - Nengsih, Warnia; Syefrida, Yulina; Guslinda, Guslinda (Caring: Jurnal Pengabdian Masyarakat, 2024)
The Community Service Program (PKM) is one of the main pillars of the Tri Dharma of Higher Education, aimed at making a tangible contribution to society. This PKM activity aims to support schools that have not yet joined the Driving School Program in implementing the Merdeka Curriculum, which is designed to provide flexibility and responsiveness to the changing times. In this effort, various activities have been designed, including the establishment of Literacy & Numeracy Clubs to enhance literacy skills, the formation of Learning Communities for teacher collaboration, and the launch of SI-Events, an information system that centrally manages school activities. Additionally, a series of workshops have been conducted to support curriculum transformation, covering the development of teaching modules, operational curricula, strengthening the Pancasila Student Profile, creating interactive teaching media, and inclusive differentiated learning. This learning approach ensures that each student receives attention according to their needs, enabling them to discover and develop their maximum potential. The results of this PKM activity demonstrate that proper guidance and practical programs can effectively assist schools in implementing the Merdeka Curriculum.